2002
DOI: 10.1111/j.1708-8240.2002.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleaching Agents on the Hardness and Morphology of Enamel

Abstract: Bleaching treatment conducted with two home bleaching agents (Opalescence 10%, Ultradent, and Hi-Lite II, Shofu) had no adverse effects on enamel microhardness or on surface morphology. Bleaching with 3% hydrogen peroxide can have a negative effect on enamel hardness and surface morphology when performed as described in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1
21

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 14 publications
8
78
1
21
Order By: Relevance
“…This is in agreement with several previous reports [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. In contrast, a few studies have reported changes in the mechanical properties of enamel [45,46,47].…”
Section: Discussionsupporting
confidence: 79%
“…This is in agreement with several previous reports [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. In contrast, a few studies have reported changes in the mechanical properties of enamel [45,46,47].…”
Section: Discussionsupporting
confidence: 79%
“…7,9,13,[19][20] However, other studies reported that 10% carbamide peroxide gel did not affect enamel surface hardness. [21][22][23] These contradictory findings among different studies might be due to differences in method, such as frequency and time of bleaching treatment, storage media or the use of human or bovine teeth.…”
Section: Discussionmentioning
confidence: 96%
“…9,27,28 However, other studies have reported different results with no statistically significant differences in tooth hard tissue characteristics, including enamel and dentin surface roughness, after bleaching with 10% and 15% carbamide peroxide. 17,18,[29][30][31] The discrepancies in the results of various studies might be attributed to differences in the formulation and concentration of bleaching agents; the duration of daily applications or treatment protocols; differences in study designs, including the environments in which the specimens are stored (eg, artificial or human saliva); the use of remineralizing agents; continuous use of fluoridated toothpastes; and the technique of toothbrushing during the procedure and after bleaching. 2,14,30,32,33 In the present study, tooth structures underwent surface changes after bleaching, and toothbrushing immediately after bleaching had a substantial role in increasing enamel surface roughness.…”
Section: Discussionmentioning
confidence: 99%